Investigating the threat of AI to undergraduate medical school admissions: a study of its potential impact on the rating of applicant essays - Joshua Choi; Jenny Zhao; Thuy-Anh Ngo; Lawrence Grierson (Canadian Medical Education Journal)
Background: Medical school applications often require short written essays or personal statements, which are purportedly used to assess professional qualities related to the practice of medicine. With generative artificial intelligence (AI) tools capable of supplementing or replacing inputs by human applicants, concerns about how these tools impact written assessments are growing. This study explores how AI influences the ratings of essays used for medical school admissions